(untitled) (New York, 2017)
Presents an introduction to the Python programming language with illustrated steps for creating simple projects, including an animal quiz, a password picker, a robot builder, and a screen pet.
Keywords: Python (Ngôn ngữ lập trình máy tính),Thuật toán máy tính,Python (Computer program language)